(untitled) (The Pakistan Development Review, 2001)
Whereas the policy incentives were designed to promote exports from Pakistan, the incentive system instead led to illicit export practices, i.e., export overinvoicing due to the weaknesses of implementation. Such practices resulted in a significant financial loss to the country and undermined the effectiveness of the export-promoting policy. This paper has determined the presence of overinvoicing of exports in Pakistan and the geographic and product-wise patterns in export overinvoicing. The paper has applied the ‘partner-country data comparison’ technique. Empirical findings confirm the strong presence of export overinvoicing across trading partner countries and products. This conclusion is further supported by the evidence of a significant difference between the duty-drawback rate and the premium on foreign exchange in the kerb market. Convincing presence of export overinvoicing is the basis for a set of policy recommendations made in the paper.